'I caught you!' Part 2: enriching the external reality. Issue 1 (2nd January 2022) - Levi, Sheila
ABSTRACT: This paper describes and explores the second part of the therapeutic treatment of a young boy who was diagnosed with autism, aged two. In the previous paper, his intensive psychoanalytic psychotherapy and his mind's growth were covered. In this paper, his non-intensive psychotherapy, parent work, a home-enrichment programme, a structured personality assessment (including use of the WISC-III UK), and mainstream integration will be reported on. The aim of this account is to argue that differential diagnosis is essential for complex cases where there is early neglect and abuse in the child's developmental history. A psychoanalytic approach that includes personality assessment is suggested to accompany, and even at times replace, the more widely used medical and behavioural assessment methods. It is argued that this can be more comprehensive and helpful in getting to the bottom of the child's psychological and developmental difficulties, and so can aid in planning effective treatment and support.